Efficient charge carrier injection and balance achieved by low electrochemical doping in solution-processed polymer light-emitting diodes - Yan,H; Limbu,S; Wang,X; Nightingale,J; Hamilton,I; Wade,J; Kwon,S; Lee,K; Kim,J-S (Advanced Functional Materials, 2019)
Charge carrier injection and transport in polymer lightemitting diodes (PLEDs) is strongly limited by the energy level offset at organic/(in)organic interfaces and the mismatch in electron and hole mobilities. Herein, these limitations are overcome via electrochemical doping of a lightemitting polymer. Less than 1 wt% of doping agent is enough to effectively tune charge injection and balance and hence significantly improve PLED performance. For thick singlelayer (1.2 µm) PLEDs, dramatic reductions in current and luminance turnon voltages (VJ = 11.6 V from 20.0 V and VL = 12.7 V from 19.8 V with/without doping) accompanied by reduced efficiency rolloff are observed. For thinner (<100 nm) PLEDs, electrochemical doping removes a thickness dependence on VJ and VL, enabling homogeneous electroluminescence emission in largearea doped devices. Such efficient charge injection and balance properties achieved in doped PLEDs are attributed to a strong electrochemical interaction between the polymer and the doping agents, which is probed by in situ electricfielddependent Raman spectroscopy combined with further electrical and energetic analysis. This approach to control charge injection and balance in solutionprocessed PLEDs by low electrochemical doping provides a simple yet feasible strategy for developing highquality and efficient lighting applications that are fully compatible with printing technologies.